How to Continue to Promote the Normalization and Institutionalization of "Two Learning and One Doing" Learning and Education in Enterprises - Wang, Yuanyuan (Journal of Theory and Practice of Contemporary Education, 2023)
Promote the normalization and institutionalization of "two learning and one doing" learning and education, focus on grasping the key minority and strengthening the grass-roots branches, take "two learning and one doing" as the basic content, take "three meetings and one lesson" as the basic system, take the Party branch as the basic unit, take solving problems and playing a role as the basic goal, integrate into daily life, focus on regular work, and form long-term effects. Party members and leading cadres should take the lead in learning and doing, take the study of the Party Constitution and regulations and the series of speeches as the main content, constantly improve and transform themselves, and practice the "four stresses and four haves" to become qualified Party members.